Wuhan and Hubei COVID-19 mortality analysis reveals the critical role of timely supply of medical resources. Issue 1 (July 2020) - Zhang, Zuqin; Yao, Wei; Wang, Yan; Long, Cheng; Fu, Xinmiao
Highlights: COVID-19 mortality rates in Wuhan and Hubei decay exponentially. COVID-19 mortality rates outside Hubei and Wuhan are nearly constant. COVID-19 recovery rates in Wuhan and Hubei grow exponentially. Over 40, 000 aided health workers help Hubei to effectively treat patients. Newly supplied beds allow over 38, 000 patients in Wuhan to be treated in hospitals. Graphic abstract: Image, graphical abstract